Hydrogel in-tape electronic tongue - Brito-Pereira, Ricardo (2025)
An electronic tongue is a sensor-based system designed to mimic human taste by detecting and analyzing the chemical properties of liquids through electrochemical methods. Here, we introduce the HITS concept, an electronic tongue system that enables rapid and sequential classification of various beverages. This system utilizes a single, cost-effective platform with interdigital electrodes made of carbon printed on recyclable poly(ethylene terephthalate) (PET), significantly reducing the need for multiple electrodes. With the use of interchangeable hydrogel tapes, the system requires a single deep (150 μL) pore per analysis, allowing for efficient sequential testing. The hydrogel seamlessly accommodates the electrode interface and operates with a semisolid electrolyte, achieving ultrafast analysis times of just 5 min. Employing AI and machine learning algorithms, HITS accurately differentiated between coffee, juice, water, white wine, and red wine with a 100% success rate. This sustainable approach combines high precision, speed, and low environmental impact, offering a versatile solution for various technological applications, including food science, quality control, and health monitoring. This e-solution not only enhances precision and speed but also aligns with growing environmental concerns, offering a low-impact and scalable platform for advanced liquid analysis.